Post-treatment of hyaluronan to decrease the apoptotic effects of carprofen in canine articular chondrocyte culture - Korakot Nganvongpanit (2020)
© Copyright 2020 Nganvongpanit et al. A major concern associated with the use of drugs is their adverse side effects. Specific examples of the drugs of concern include antibiotic agents and non-steroidal anti-inflammatory drugs. Despite the presence of a high degree of efficacy for specific conditions, these drugs may deteriorate the surrounding tissues that are exposed to them. Often, carprofen is used for joint inflammation; however, it may stimulate cartilage degradation which can then lead to osteoarthritis progression. In this study, hyaluronan was combined with carprofen treatment in three different applications (pre-treatment, co-treatment and post-treatment) on normal canine chondrocytes to determine whether Hyaluronan (HA) is capable of mitigating the degree of chondrotoxicity of carprofen. Our findings revealed that carprofen at IC20 (0.16 mg/mL) decreased viability and increased nitric oxide (NO) production. Importantly, carprofen induced the apoptosis of canine chondrocytes via the up-regulation of Bax, Casp3, Casp8, Casp9 and NOS2 as compared to the control group. Although the co-treatment of HA and carprofen appeared not to further alleviate the chondrotoxicity of carprofen due to the presence of a high number of apoptotic chondrocytes, post-treatment with HA (carprofen treatment for 24 h and then changed to HA for 24 h) resulted in a decrease in chondrocyte apoptosis by the down-regulation of Bax, Casp3, Casp8, Casp9, NOS2, along with NO production when compared with the treatment of carprofen for 48 h (P < 0.05). These results suggest that HA can be used as a therapeutic agent to mitigate the degree of chondrotoxicity of carprofen.